Optimizing the Use of Practical Methods to Improve Skills in Creating 2D and 3D Animations - Subiyantoro, Singgih; Yuliana, Mita; Nurbaiti, Nita; Ramadhani, Sari Aisyah; Murti, Wandha Prayuda (Edutech Publishing Media, 2023)
Practice is a learning method that involves students directly in developing specific skills. Objectively, there are many advantages and disadvantages of using practical methods in learning. This research aims to improve students' skills in creating 2D and 3D animations through the use of practical methods. The research method used is Classroom Action Research (PTK) by adopting the Kemmis & Tagart model. The subjects of this study were students in class 11 A majoring in Multimedia at a Vocational High School (SMK) in Indonesia who were making 2D and 3D animations. Data was collected using observation sheets, interview guides, and portfolios. The research results show that the practical method is able to improve students' skills in creating 2D and 3D animations. The observation results showed that there was an increase in students' skills, namely by (7.01%) after using practical methods rather than just theory. The results of interviews and analysis of the portfolio also show data that is relevant to the results of these observations. In conclusion, the use of practical methods has proven to be effective in improving students' skills in creating 2D and 3D animations. Overall, this research contributes to solving learning problems, especially the low skills of students in making 2D and 3D animations which are commonly found in Vocational High Schools.